STEP-UP OF STUDENTS’ WRITING SKILL BY USING A SILLY SENTENCE SLIDERS - Nazariani Nazariani (Department of English Education, Faculty of Teacher Training and Education, Almuslim University, 2023)
The title of this research is Step-Up of Students’ Writing Skill by Using A Silly Sentence Sliders (Lesson Study Based at SMAN 1 Kutablang). The purpose of this research is to find out how the use of silly sentence sliders in lesson study step-up the students’ writing skills and to find out how a silly sentence slider show the process of the students’ writing skill. The method utilized in this research is qualitative approach with lesson study design. The population of this research was the second-grade students at SMAN 1 Kutablang. Meanwhile, the sample that the researcher took was class 11 MIA 2 with the total of 19 students in the classroom. In the part of the technique in data collection, the researcher used observation sheet, test, and documentation as the instruments. Based on the research process that was done, the researcher found out that the students' ability to understand how to write English writing was low in the pre-test than in the post-test. The pre-test result showed that the student's average score was 1.180 and the percentage of students who score up to the score of 70 was only 9 students or 47% of the total students who took the test, and the remain 10 students were categorized as failed. Meanwhile, in the post-test after the researcher applied the action, the researcher found that the students’ average score was 1.620. It can be seen that the students' scores in writing skills have increased. The percentage of students who passed with scores of 70 or above were 19 students. Therefore, the post-test was categorized as successful. The research data was analyzed by using modified scoring rubric according to Heaton in Uztosun (2006).